Differentiation of benign and malignant nasopharyngeal lesions based on FDG uptake on PET/CT: comparison with pathology - (:unkn) unknown (AVES, 2020)
Objeotive: The incidental fluor'ine19-fluorodeoxygfticose (FDG) uptake on pos'itron emission tomography4Don-Iputerized tomography (PET/CT) patents who Liederg,o st.;bsegjent nasopharyngeal biopsy tor SLiSpecteci nasopharyrIgeai malignancy has not bee n assessed_ The O. O50 of this study was to dete:mine the 30 ty of EDG maximum standa:dized uptake value on PET/CT to differentiate betWeen bet; g ptoceSSeS and 'a 'g nasophatyngeal Methods: We retrospectiveiy tevieWed the m so' or records of 92 patier:ts who Underwent ECG PET/CT for diseases odlet than i'lasop geai with subsequent enclos
Keywords: Biopsy; nasopharyngeal carcionma; PET/CT; POSITRON-EMISSION-TOMOGRAPHY; F-18-FDG PET; CARCINOMA; HEAD; NECK; IMPACT; SCANS; TUMOR